CHARACTERIZATION OF NOVEL EDIBLE FILM FROM DEAMIDATED RICE (Oryza sativa) BRAN PROTEIN - Osman, M. F.; Asiri, S. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate the characteristics of new edible film prepared from deamidated rice bran protein (RBP). Deamidation was carried out at temperatures of 80, 100, and 120°C under varying pH conditions of 8, 10, and 12 for durations of 15 and 30 minutes to enhance protein solubility. The resulting film was then assessed for its physical, mechanical, and optical properties. The results revealed that protein solubility of deamidated RBP improved across all temperatures and pH levels compared to the control. A film made from deamidated protein under conditions of 120°C and pH levels of 8, 10, and 12 was evaluated using protein concentrations of 3, 4, and 5%. The solubility of the film increased as the pH was raised from 8 to 12 compared to the control. Swelling also increased with a higher protein percentage. However, films prepared through deamidation at pH levels of 10 and 12 at 120°C became fully soluble in water and completely dissolved. The puncture strength of deamidated, control, and SBP films increased as the RBP concentration rose from 3% to 5%. Among all RBP films, the deamidated (D) film exhibited the highest puncture strength, although it was still lower than that of the soybean protein (SBP) film. The elongation also improved with the increase in puncture strength. The opacity of RBP films increased with higher protein levels but remained lower than that of the control.